PERENCANAAN DIMENSI KANTONG LUMPUR PADA INTAKE DAERAH IRIGASI CIHAREWOS - Insan Fadil Insan Fadil; Feril Hariati; Alimuddin Alimuddin (Universitas Kristen Maranatha, 2022)
The Ciharewos River was affected by the Cidurian flood, resulting in a pile of sediment along the river channel, precisely behind the Ciharewos Dam building which resulted in the water quality of the Ciharewos Irrigation Area declining. The purpose of this study was to obtain the rate of floating sediment transport that would enter the intake using the Meyer Petter and Muller method. Next, plan the dimensions of the mud bag from the results of the sediment rate that has been obtained. The research phase begins by testing the suspended load and the base sediment sample, the flow velocity, and the required dimensions of the mud bag. The results of the analysis using the Meyer Petter and Muller method obtained a sediment rate discharge value of 3.04 m3/day. With a rinse time of fourteen (14) days, the volume of the mud bag required is 42.68 m3. The planning for the dimensions of the mud bag is carried out three (3) times with a minimum design water velocity limit (vn) of 0.30 m/s to 1.470 m/s, and a design channel width (bn) of 1.00 to 2.00 meters, so that the most economical ratio of mud bag dimensions is obtained. The most economical mud bag dimensions are obtained from Simulation III with design speed (vn) 0.30 m/s, design channel width (bn) 2.00 meters, height (hn) 0.76 meters, and length (L) 25, 47 meters.